Regional intra-arterial chemotherapy in advanced cancer - Priario, Julio C; Iriondo, Luis S; Kasdorf, Helmut (Cirugía del Uruguay, 2020)
A study of the method of regional intra-arterial infusion of antineoplastic chemical agents was carried out in 14 patients in whom 16 infusions were carried out.